The Gargling Lime Juice (Citrus aurantifolia) and Plaque Index in Adolescent Girls Aged 18-20 Years: A Pseudo-Experimental Study - Anneke Tahulending; Jeanne d’arc Zafera Adam; Jeineke Ellen Ratuela; Rabia Ani Ohoirat; Oksfriani Jufri Sumampouw (Sam Ratulangi Journal of Public Health, 2024)
Background: Plaque is a soft deposit that sticks tightly to the surface of the teeth. Plaque can be controlled by regular brushing and the use of mouthwash. Plaque control by gargling can use traditional plant materials, one of which is lime (Citrus aurantifolia). Lime contains compounds that are antibacterial, namely essential oils that can inhibit the growth of bacteria plaque formation. One of the populations with dental and oral health problems is adolescents. The purpose of this study is to measure the effect of gargling lime juice (Citrus aurantifolia) on plaque index in adolescent girls aged 18-20 years. Methods: This is a pseudo-experimental research. The pre-experimental design used is one group pre testpost test design. This research was carried out in May 2024 in Manado City. A total of 42 female remakami aged 18-20 years were sampled in this study. The variable measured was the plaque index. The treatment given is gargling with lime juice. The instruments of this research are a set diagnostic tool, and a plaque index examination format. The research material is lime juice. The data obtained, tabulated and then analyzed using the paired sample t-test. Research Results: The results showed that the average plaque index before gargling with lime juice is 2.1809 and after gargling is 0.3357. There was a difference in the decrease in plaque index before and after gargling lime juice, which was 1.8452. The results of the paired t-test sample obtained a significance value of 0.000. This value shows that there is a significant difference in plaque index between subjects who gargle with orange leaf decoction and those who do not. Conclusion: It can be concluded that the habit of gargling with lime juice can reduce plaque index in adolescent girls aged 18-20 years in Manado city.